Advanced Catalytic Performance of Au–Pt Double‐Walled Nanotubes and Their Fabrication through Galvanic Replacement Reaction. Issue 35 (12th July 2013) - Chen, Lu; Kuai, Long; Yu, Xue; Li, Wenzheng; Geng, Baoyou
Abstract Bimetallic tubular nanostructures have been the focus of intensive research as they have very interesting potential applications in various fields including catalysis and electronics. In this paper, we demonstrate a facile method for the fabrication of Au–Pt double‐walled nanotubes (Au–Pt DWNTs). The DWNTs are fabricated through the galvanic displacement reaction between Ag nanowires and various metal ions, and the Au–Pt DWNT catalysts exhibit high active catalytic performances toward both methanol electro‐oxidation and 4‐nitrophenol (4‐NP) reduction. First, they have a high electrochemically active surface area of 61.66 m2 g−1, which is close to the value of commercial Pt/C catalysts (64.76 m2 g−1), and the peak current density of Au–Pt DWNTs in methanol oxidation is recorded as 138.25 mA mg−1, whereas those of Pt nanotubes, Au/Pt nanotubes (simple mixture), and commercial Pt/C are 24.12, 40.95, and120.65 mA mg−1, respectively. The Au–Pt DWNTs show a markedly enhanced electrocatalytic activity for methanol oxidation compared with the other three catalysts. They also show an excellent catalytic performance in comparison with common Au nanotubes for 4‐nitrophenol (4‐NP) reduction. The attractive performance exhibited by these prepared Au–Pt DWNTs can be attributed to their unique structures, which make them promising candidates as high‐performance catalysts.